2010
DOI: 10.1246/bcsj.20090342
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure of Boron Compounds Bearing Tridentate Ligands with 1,3-Bicarbonylbenzene Skeleton

Abstract: In order to examine differences in structure due to the electronic nature of the oxygen ligand, several organoboron compounds bearing ester 8a–8c and amide 13a and 13b ligands were prepared and crystallographically analyzed. In the ester ligand systems, the pinacolato derivative 8a and catecholato derivative 8b took a pentacoordinate structure, while fluorenyl derivative 8c took a tetracoordinate structure instead of pentacoordinate due to the strong electrophilic nature of the boron atom. In contrast to the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…The geometries and relative stabilities of the singlet and triplet states of 8a (A = S) and 8b (A = NMe) were calculated at the B3PW91/6‐31G(d) level . The triplet states ( 8a T and 8b T , respectively) were found to be favored over the corresponding closed‐shell singlet states ( 8a CS and 8b CS , respectively) for both compounds (Δ E ST = E CS − E T = 12.6 and 14.0 kcal/mol for 8a and 8b , respectively).…”
Section: Resultsmentioning
confidence: 99%
“…The geometries and relative stabilities of the singlet and triplet states of 8a (A = S) and 8b (A = NMe) were calculated at the B3PW91/6‐31G(d) level . The triplet states ( 8a T and 8b T , respectively) were found to be favored over the corresponding closed‐shell singlet states ( 8a CS and 8b CS , respectively) for both compounds (Δ E ST = E CS − E T = 12.6 and 14.0 kcal/mol for 8a and 8b , respectively).…”
Section: Resultsmentioning
confidence: 99%
“…The formation of metal halide byproducts provides a driving force for the reaction and can be easily removed due to their poor solubility in nonpolar solvents. It has been demonstrated that treating 9-halo-9-borafluorenes ( 2 or 45 ) with lithium (di- tert -butylboryl)­methylamide, 2,4,6-tri tert -butylphenyl lithium (Mes*Li), Li­[P­( t Bu) 2 ], potassium bis­(trimethylsilyl)­amide (K­[N­(SiMe 3 ) 2 ]), , 2,4,6-tris­(trifluoromethyl)­phenyl lithium (Mes F Li), , LiF, t BuONa, t BuOK, bis­(methylthio)­lead [Pb­(SCH 3 ) 2 ], chloromercuri­ferrocene (FcHgCl) and bis­(cyclopentadienyl)­zirconium­(IV) dimethyl (Cp 2 ZrMe 2 ) can generate the corresponding 9-borafluorenes ( 66 – 75 ) in moderate to good yields (Table , entries 1–12).…”
Section: Synthesismentioning
confidence: 99%
“…In particular, reaction of BCl 3 with [Li 2 (ttp)] (ttp: tetra(p-tolyl)porphyrin) gives the corresponding diboryl complex, which can be reduced with two equivalents of a Na/K alloy to yield the dichlorodiboranyl complex. A subsequent chloride abstraction with Na[BAr 60 [26] 2+ can be also viewed as a borenium dimer linked through a B(sp 2 )B(sp 2 ) bond. Unfortunately, structural characterization of [26] 2+ could not be accomplished due to the high Lewis acidity of the molecule.…”
Section: N-coordinated Diboron Dication Analogues [L(h)b(¯2-h) 2 B(h)l]mentioning
confidence: 99%
“…A subsequent chloride abstraction with Na[BAr 60 [26] 2+ can be also viewed as a borenium dimer linked through a B(sp 2 )B(sp 2 ) bond. Unfortunately, structural characterization of [26] 2+ could not be accomplished due to the high Lewis acidity of the molecule.…”
Section: N-coordinated Diboron Dication Analogues [L(h)b(¯2-h) 2 B(h)l]mentioning
confidence: 99%